Kegiatan Ekstrakurikuler Gitar Menggunakan Media Video Lessons Di SMP Negeri 8 Padang - Irwan Rahmat Putra; Syahrel Syahrel; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2014)
Abstract This study was aimed conducting an extracurricular activity with a new method, so it can trigger students to participate in this activity. This a a qualitative study with descriptive-analysis method. It was intended to describe the implementation of guitar extracurricular activity at SMPN 8 Padang. The data were collected through observation, interview, documentation, and library study. The result revealed that guitar extracurricular activity at SMPN 8 Padang was carried out by using video lessons media in order to improve students’ creativity in playing musical instrument.Thus, it can be concluded that (1) its guitar curricular activity ran well, but needs some improvement; (2) video lessons media was expected to be able to motivate student to participate n this activity; (3) student can play simple song by using guitar either individually or in grup; (4) student were able to express and perform their ability in school activities; (5) student could get good achievement in many music competitions. Key word: Extracurricular, guitar, video lessons